2015
DOI: 10.1007/s00586-015-3939-5
|View full text |Cite
|
Sign up to set email alerts
|

An 11-year minimum follow-up of the Charite III lumbar disc replacement for the treatment of symptomatic degenerative disc disease

Abstract: Purpose To report our 11-year minimum clinical and radiological outcomes, as well as complications of the Charite III total disc replacement (TDR). Methods A total of 35 patients indicated for total disc replacement were implanted with the Charite III prosthesis. Clinical evaluation included visual analog scale (VAS) for back pain and the Oswestry disability index (ODI). Radiological parameters of intervertebral disc height (IDH), range of motion (ROM), lumbar lordosis, lumbar scoliosis and prosthesis position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 50 publications
(50 reference statements)
0
39
0
Order By: Relevance
“…Postfusion pain is independent of factors such as poor posture, paraspinal muscle pain, or pseudoarthrosis, and showed a signi cant correlation with sagittal imbalance such as decreased ST, increased pelvic tilt and decreased LL. [17] Our previous study on better treatment options in patients with DDD has led us to the discovery of a more preferable option of motion-preserving total disc arthroplasty [6,7] , avoiding fusion. But to our knowledge, the effect of TDR with Activ L on sagittal alignment has not been studied till date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postfusion pain is independent of factors such as poor posture, paraspinal muscle pain, or pseudoarthrosis, and showed a signi cant correlation with sagittal imbalance such as decreased ST, increased pelvic tilt and decreased LL. [17] Our previous study on better treatment options in patients with DDD has led us to the discovery of a more preferable option of motion-preserving total disc arthroplasty [6,7] , avoiding fusion. But to our knowledge, the effect of TDR with Activ L on sagittal alignment has not been studied till date.…”
Section: Discussionmentioning
confidence: 99%
“…Siepeet al [5] have prospectively analyzed the clinical e cacy of TDR with ProDisc II (DePuySynthes Inc., West Chester, PA, USA), and the results revealed satisfactory and maintained mid-to long-term clinical outcomes after a mean follow-up of 7.4 years. The midterm results of TDR with SB Charité III (DePuySynthes Inc.) prosthesis [6] and clinical results of 1-to 3-year follow-up with activ L arti cial disc (Aesculap AG & Co. KG, Tuttlingen, Germany) [7] have been reported previously, and revealed satisfactory clinical outcomes in both patient cohorts. However, a ve-year, prospective, randomized multicenter study showed no signi cant differences in the clinical outcomes between TDR and fusion.…”
Section: Introductionmentioning
confidence: 98%
“…There is no current conclusive evidence of LDA superiority in the long-term in level I studies and the surgery is technically more challenging. However, mid-term studies of LDA have reported satisfactory clinical results and implant survival and comparable complication profiles to fusion [9394] with proponents of LDA supporting its use for several theoretical and clinical advantages.…”
Section: Operative Treatmentmentioning
confidence: 99%
“…Complication rates, while reported to be lower than fusion in the Charité trials (29.1% for arthroplasty and 50.2% for fusion at 2-year follow-up), are still significant [113]. These can be broadly separated into those related to the anterior surgical approach (e.g., vascular injury, nerve root injury, retrograde ejaculation), prosthesis/fusion failure (e.g., subsidence, osteolysis, migration, implant fracture, endplate fracture, pseudoarthrosis), heterotopic ossification (up to 76% at 3 years) and subsequent hypomobility of the implant and donorsite complications [93]. Device failures necessitating repeat operations have been reported at 5.4% to 6.3%.…”
Section: Operative Treatmentmentioning
confidence: 99%
“…However, TDR may have serious drawbacks [10][11][12], such as subsidence, facet joint degeneration, dislocation or malposition of the implant, requiring surgical revision [13][14][15][16]. According to the literature, 6-14% of patients needed revision fusion surgery after TDR [10,11,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%